1996
DOI: 10.1055/s-0038-1650254
|View full text |Cite
|
Sign up to set email alerts
|

Upper Extremity Deep Venous Thrombosis in Cancer Patients with Venous Access Devices - Prophylaxis with a Low Molecular Weight Heparin (Fragmin)

Abstract: SummaryCentral venous access devices are often essential for the administration of chemotherapy to patients with malignancy, but its use has been associated with a number of complications, mainly thrombosis. The true incidence of upper extremity deep vein thrombosis (DVT) in this setting is difficult to estimate since there are very few studies in which DVT diagnosis was based on objective tests, but its sequelae include septic thrombophlebitis, loss of central venous access and pulmonary embolism.We performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
224
2
12

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(245 citation statements)
references
References 10 publications
7
224
2
12
Order By: Relevance
“…[23][24] Recently, in a randomised controlled trial, we showed that low-dose of UFH was safe and effective to prevent CVC-related thrombosis in patients with haemato-oncological disease. 25 However, many clinicians are reluctant to prescribe anticoagulant prophylaxis routinely in patients with cancer and a CVC because of the low expected incidence of thrombosis and the fear of bleeding during anticoagulant prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24] Recently, in a randomised controlled trial, we showed that low-dose of UFH was safe and effective to prevent CVC-related thrombosis in patients with haemato-oncological disease. 25 However, many clinicians are reluctant to prescribe anticoagulant prophylaxis routinely in patients with cancer and a CVC because of the low expected incidence of thrombosis and the fear of bleeding during anticoagulant prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 92 patients with implanted devices managed with heparin flushes and, in high-risk patients, a low-dose oral anticoagulant, Lokich et al reported a 16% thrombosis rate, which they contrasted with the 43% thrombosis rate in a previous series of patients with tunneled subclavian catheters [17]. Thrombosis rates of 37%-62% were observed in the control groups of two small trials [18,19].…”
Section: Venous Thrombosis In Cancer Patientsmentioning
confidence: 96%
“…In North America, fixed low-dose oral anticoagulants were the more common treatment. Both of these strategies are supported by small prospective studies [18,19]. In the event that thrombosis developed when a central venous access device was in use, most physicians favored removal of the device and additional therapy.…”
Section: Venous Thrombosis In Cancer Patientsmentioning
confidence: 99%
“…Neither bleeding events nor information on the degree of thrombocytopenia and dose interruptions were reported in this retrospective trial. 26 Similarly, the use of very-low-dose warfarin (ie 1-mg daily) for the prevention of CVC-TE in thrombocytopenic cancer patients was either not fully described 27,28 or discontinued when platelets were below o50 Â 10 9 /l. 29 In clinical practice, practitioners are inclined to empirically withhold antithrombotic therapy until platelet count is above 50 Â 10 9 /l for fear of bleeding.…”
Section: Discussionmentioning
confidence: 99%